2023
DOI: 10.1017/s0950268823001826
|View full text |Cite
|
Sign up to set email alerts
|

Association between face mask use and risk of SARS-CoV-2 infection: Cross-sectional study

Ingeborg Hess Elgersma,
Atle Fretheim,
Petter Elstrøm
et al.

Abstract: We examined the association between face masks and risk of infection with SARS-CoV-2 using cross-sectional data from 3,209 participants in a randomized trial exploring the effectiveness of glasses in reducing the risk of SARS-CoV-2 infection. Face mask use was based on participants’ response to the end-of-follow-up survey. We found that the incidence of self-reported COVID-19 was 33% (aRR 1.33; 95% CI 1.03–1.72) higher in those wearing face masks often or sometimes, and 40% (aRR 1.40; 95% CI 1.08–1.82) higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…In short, the adverse effects of masks are clear [2,3,5,15,17,19,20,24,37,124,[158][159][160][161][162][163][164]179], whereas the protective antiviral effect in real life scenarios remains doubtful [13][14][15][16]157,[180][181][182][183][184][185][186][187][188][189][190][191][192][193][194][195][196][197][198]. Given this, together with the microbiological contamination issues highlighted, masking laws and requirements do not meet the basic medical ethic of 'Do no harm'.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In short, the adverse effects of masks are clear [2,3,5,15,17,19,20,24,37,124,[158][159][160][161][162][163][164]179], whereas the protective antiviral effect in real life scenarios remains doubtful [13][14][15][16]157,[180][181][182][183][184][185][186][187][188][189][190][191][192][193][194][195][196][197][198]. Given this, together with the microbiological contamination issues highlighted, masking laws and requirements do not meet the basic medical ethic of 'Do no harm'.…”
Section: Discussionmentioning
confidence: 99%
“…For masks to be demanded, the side effects and risks must be lower than the risk of not wearing a mask. A gold-standard Cochrane evaluation, based on clinical trials [13] found no substantive evidence of efficacy in preventing viral respiratory infections and one recent study, albeit with several possible confounders, even found mask-wearing to be associated with an increased risk of COVID-19 infection [157]. On the other hand, the potential harms are numerous [2,3,5,[15][16][17][20][21][22][23][24]37,38,[158][159][160][161][162][163][164].…”
Section: Findings In Contextmentioning
confidence: 99%